Preparation of glutinous rice starch/polyvinyl alcohol copolymer electrospun fibers for using as a drug delivery carrier - Patthanakorn Jaiturong (2018)
© 2017. Glutinous rice starch (GRS) is commonly produced in the Northeast of Thailand. GRS is a biopolymer which is widely used in the food industry but not yet commonly applied within the pharmaceutical industry as an alternative resource. GRS exhibits a branch chain structure which is not feasible to fabricate as nanofiber. Therefore, combining GRS with polyvinyl alcohol (PVA) in hybrid form can be a potential platform to produce GRS-PVA nanofibers. Smooth nanofibers of 2% (w/v) GRS combined with 8% (w/v) PVA were fabricated by an electrospinning process. A scanning electron microscope (SEM) revealed an average diameter size of the GRS-PVA nanofibers equal to 191 ± 25 nm. A highly water soluble model drug, Chlorpheniramine maleate (CPM), was incorporated into the GRS-PVA electrospun fibers to prove a drug delivery carrier concept and drug release control of the nanofibers. The GRS-PVA nanofibers exhibited a biphasic CPM release in which approximately 60% of the drug immediately released in 10 min, and it reached 90% drug release in 120 min. This study demonstrated a potential application of GRS combining with PVA as an oral drug delivery carrier. Therefore, it can be a promised step that expands the application GRS in pharmaceuticals and related areas.